A study of the clinical profile of acute pancreatitis and its correlation with severity indices - Krishnamoorthy, Vengadakrishnan; A.K, Koushik (International Journal of Health Sciences, 2015)
Background: Acute pancreatitis is a common disease with wide clinical variation and its incidence is increasing. Acute pancreatitis may vary in severity, from mild self-limiting pancreatic inflammation to pancreatic necrosis with life-threatening sequelae. Severity of acute pancreatitis is linked to the presence of systemic organ dysfunctions and/or necrotizing pancreatitis. Aim and objectives: The present study was aimed to assess the clinical profile of acute pancreatitis and to assess the efficacy of various severity indices in predicting the outcome of patients. Methodology: This was a prospective study done in Sri Ramachandra Medical College and Hospital from April 2012- September 2014. All patients with a diagnosis of acute pancreatitis were included in this study. Along with routine lab parameters, serum amylase, lipase, lipid profile, calcium, CRP, LDH, CT abdomen, CXR and 2D Echo was done for all patients. Results: A total of 110 patients were analysed. 50 patients required Intensive care, among them 9 patients (18%) died. 20 patients (18.2%) had MODS, 15 patients (13.6%) had pleural effusion, 9 patients (8.2%) had pseudocyst, 2 patients(1.8%) had hypotension, 2 patients(1.8%) had ARDS and 2 patients(1.8%) had DKA. In relation to various severity indices, high score of CRP, LDH and CT severity index was associated with increased morbidity and mortality. 15 patients (13.6%) underwent open necrosectomy surgery, 3 patients (2.7%) underwent laparoscopic necrosectomy and 7 patients (6.4%) were tried step up approach but could not avoid surgery. Step up approach and surgery did not have a significant reduction in the mortality. Conclusion: Initial assessment of severity by CRP, LDH and lipase could be reliable indicators of outcome in acute pancreatitis